Inflammatory bowel disease course in liver transplant versus non-liver transplant patients for primary sclerosing cholangitis: LIVIBD, an IG-IBD study. Issue 6 (June 2021) - Ribaldone, Davide Giuseppe; Imperatore, Nicola; Le Grazie, Marco; Furfaro, Federica; Balestrieri, Paola; De Blasio, Federico; Fagoonee, Sharmila; Mosso, Elena; Boano, Valentina; Reggio, Dario; Sarli, Ennio; Castiglione, Fabiana; et al.
Abstract: Background: Data regarding the effect of orthotopic liver transplantation (OLT) for primary sclerosing cholangitis (PSC) on inflammatory bowel disease (IBD) course are scarce and conflicting. Aims: To compare the incidence of refractory IBD in two groups (OLT and non-OLT) of patients affected by IBD and PSC. Methods: An observational, multicentre, cohort retrospective study was conducted by the Italian Group for the study of IBD in Italy. The primary outcome was the need for biologic therapy or bowel resection for medically refractory IBD or hospitalization due to IBD relapse during the follow-up. Secondary outcomes were rate of colonic dysplasia, colorectal cancer, other solid tumours, lymphoma. Results: Eighty-four patients were included in the study. The primary outcome was not different between OLT and non-OLT groups (11/27, 40.7%, versus 20/57, 35.1%, respectively, p = 0.62). The lymphoma and other tumours (thyroid cancer, kidney cancer, ileal tumour, ovarian cancer, cervical cancer) rates were significantly higher in the OLT group ( p = 0.04 and p = 0.005, respectively), at the limit of statistical significance for high-grade colonic dysplasia ( p = 0.06). Conclusion: OLT in patients affected by IBD and PSC is not a risk factor for a more severe IBD course, but it is associated with a higher occurrence of cancer.